Women and politics in Sri Lanka : a comparative perspective - Kiribamune, Sirima; International Centre for Ethnic Studies (Kandy : International Centre for Ethnic Studies, 1999)
Contributed articles.
Keywords: Women -- Political activity -- Sri Lanka; Women in development -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-